PENGELOLAAN SANITASI MAKANAN DAN LINGKUNGAN TEMPAT TINGGAL BERBASIS PENDIDIKAN KARAKTER SEBAGAI UPAYA PENINGKATAN KUALITAS HIDUP SANTRI - Supratno, Haris (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2016)
Pesantren has very important role in improving the santri quality life through managing food and dwelling sanitation. By healthy, hygienic, and nutritious food and also good dwelling, it can improve santri quality life. Generally, some Pesantren in Jombang district have not been managed their food and environment dwelling well. They also have not been fulfilled the medical standard, especially, some small and traditional Pesantren. While in some big and modern Pesantren, generally have managed food and environment dwelling sanitation well and have fulfilled the medical standard. Key words: Education, medical, environment, Pesantren, sanitation, water, garbage, waste, productivity